Melodramatic Masculinity, National Identity, and the Stalinist Past in Postsoviet Cinema - Susan Larsen (Studies in 20th & 21st Century Literature, 2000)
The genre of melodrama, sweepingly scorned by Soviet film critics, proved a convenient screen vehicle for a distinctively Postsoviet imagination responding to the historical and social conundrums of the 1990s. Retrospection dominated the decade's most distinctive films, which enlisted melodramatic conventions to identify heroic Russian masculinity as the principal victim of Stalinist evil. In an intersection of national, historical, and sexual identities, directors of different backgrounds and generations collapsed feminine and Stalinist "nature" into one. Illustrative of this trend were three of the period's best known and most provocative films: Petr Todorovskii's Encore, Again, Encore (1992), Ivan Dykhovichnyi's Moscow Parade (1992), and Sergei Livnev's Hammer and Sickle (1994), which, their stylistic dissimilarities notwithstanding, all feminized Stalinism while attempting to salvage a troubled masculinity.
Keywords: Soviet Union; Russia; melodrama; society; Russian masculinity; masculinity; feminine; Stalin; Petr Todorovskii; Encore Again Encore; Ivan Dykhovichnyi; Moscow Parade; Sergei Livnev; Hammer and Sickle; feminized Stalinism